Software engineering for modern Web applications : methodologies and technologies 2026-02-15T20:46:55+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Brandon, Dan, 1946 (Information Science Reference, 2008)

(untitled)
"This book presents current, effective software engineering methods for the design and development of modern Web-based applications"--Provided by publisher